The Antiplasmodial Selectivity Index of the Alkaloid fractions of Phyllanthus Amarus, Nuclea Latifolia and Polyalthia Longifolia (African Journal of Biomedical Research, 2023)
About 60-80% world population relies on plant based medicines which are used in traditional health care systems. It is now known that, the medicinal values of these plants lies in their bioactive phytochemical constituents which produce definite physiological effects on human body. These natural compounds formed the base of modern drugs as used today. Therefore, this study seeks to evaluate the in vitro antiplasmodial activity of the phytochemicals in three herbal plants used to treat malaria and associated fever in Nigerian medicine. The three herbal plants (Phyllantus amarus, Nuclea latifolia and Polyalthia longifolia) were authenticated and their leaves were used to prepare the phytochemical extracts (alkaloid, tannin, flavonoid, saponin, glycosides and anthraquinone). Then, In vitro antiplasmodial activity of the extracts was assessed using 3D7 chloroquine sensitive strain of Plasmodium falciparum maintained at 5% hematocrit (human type O-positive red blood cells) in complete RPMI 1640 medium, while cytotoxicity was determined by the micro-assay technique using L929 animal cell fibroblasts and the lactate dehydrogenase method. Results indicate that the alkaloid fractions of P. amarus and N. lafifolia had the highest same activity (IC50:3µg/ml, CC50: 45µg/ml and SI: 15), and P. longifolia next (SI=13), while, the glycoside fraction of all three plants and the anthraquinone fraction of P longifolia and N. latifolia had least activity (SI=1 in all) when compared with the other phytochemical extracts from the three plants. All the phytochemical extracts showed no toxicity against the animal cell fibroblasts with CC50 values ranging from 20µg/ml to 63µg/ml.
Keywords: Malaria; Phytochemicals; Plasmodium; Selectivity index; Alkaloid